A pan-European survey of students’ and teachers’ digital practices in and out of the CLIL classroom: Spain A Report by CLILNetLE WorkingGroup 4 - Segura, Marta; Bárcena-Toyos, Patricia (CLILNetLE, 2024)
IntroductionThe DLSS was administered between April and May 2024 in different regions of Spain, namely Catalonia, Asturias, Cantabria, Basque Country, and Madrid. We obtained responses from 173 students in primary and secondary education schools. School administratorsand/or teachers were contacted by the researchers via email or phone to recruit the student participants.Due to Spain’s organisation in autonomous regions, different procedures were followed to access the schools to collect data with underaged students. For instance, in Catalonia, where CLIL has been widely implemented for over three decades (Departament d’Educació de la Generalitat de Catalunya, 2019), a formal request had to be submitted to the local government to obtain permission to access schools (Departament d’Educació de la Generalitat de Catalunya, 2020). Once such permission was granted, the researchers were able to contact the schools to recruit the student participants. Our student participants in Catalonia came from six different schools of different types: two public, three semi-private, and one international. The public and semi-private schools implemented CLIL from Grade 3 in primary onwards, while the international school had English as the main language of instruction through all grades.
Keywords: CLIL classroom; digital practices; education survey